Determination of flavonoid content of ethanol and ethyl acetate extract from purple passion fruit peel - Siti Delta Aisyah; Khoirul Ngibad (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
Purple passion fruit is a fruit that is widely cultivated in Indonesia for syrup and juice making. Purple passion fruit has a high nutritional value, such as antioxidants. Passion fruit contains vitamin A, vitamin C, β-carotene, flavonoid, and fiber components. However, passion fruit peel is a waste that can not be appropriately facilitated, so it becomes a waste that can pollute the environment. In addition, the passion fruit peel contains flavonoids that can be used as antidiabetic drugs. This study aimed to determine the difference in flavonoid levels in the peel extract of purple passion fruit by using ethanol and ethyl acetate solvents. The total flavonoid test using the AlCl3 method is then read on a UV-Vis spectrophotometer. The results showed total flavonoid levels of passion fruit peel extract with ethanol and ethyl acetate solvents of 15.01 mg QE/g samples and 1.27 mg QE/g extract. The highest total flavonoid levels were obtained in ethanol extract of 15.01 mg QE/g extract.